Temperature Measurement Method Based on Riesz Transform Method. (11th December 2013) - Zada, Sara; Darfi, Salah; Dembele, Vamara; Rachafi, Said; Nassim, Abdelkarim
Abstract : A method to measure the temperature of a metal plate is presented using a Riesz transform method and the monogenic signal to extract the optical phase distribution from a fringe pattern from which one can get the unknown temperature. The performance of this method is evaluated by the RFSIM metric obtained from the 2nd-order Riesz transform. A phase distribution with a good accuracy is provided.